THE QUESTION OF TEACHING CHINESE GRAMMAR AT THE INITIAL STAGE - Pak Ksenia Evgenievna (International Engineering Journal For Research & Development, 2022)
This article discusses the features of teaching Chinese grammar to students at the initial stage, the importance of teaching the grammatical aspect is noted, the results of the study are reflected, as well as on the basis of the research done and the generalization of scientific materials, recommendations for teaching and forming grammatical skills are developed.